2021
DOI: 10.1038/s41467-021-24373-5
|View full text |Cite
|
Sign up to set email alerts
|

SS18 regulates pluripotent-somatic transition through phase separation

Abstract: The transition from pluripotent to somatic states marks a critical event in mammalian development, but remains largely unresolved. Here we report the identification of SS18 as a regulator for pluripotent to somatic transition or PST by CRISPR-based whole genome screens. Mechanistically, SS18 forms microscopic condensates in nuclei through a C-terminal intrinsically disordered region (IDR) rich in tyrosine, which, once mutated, no longer form condensates nor rescue SS18−/− defect in PST. Yet, the IDR alone is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…With this in consideration, we speculated that SS18 acquired a characteristic of phase separation to participate in specific physiological functions in Chordata in the process of evolution. Interestingly, a recent study showed that SS18 mediates CBAF assembly through phase separation to regulate pluripotent-somatic transition, consistent with our speculation 32 . In their study, the authors found that a C-terminal intrinsically disordered region of SS18 regulates its forming microscopic condensates under the condition of ectopic overexpression, and that the N-terminal 70aa of SS18 is required for its binding to CBAF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With this in consideration, we speculated that SS18 acquired a characteristic of phase separation to participate in specific physiological functions in Chordata in the process of evolution. Interestingly, a recent study showed that SS18 mediates CBAF assembly through phase separation to regulate pluripotent-somatic transition, consistent with our speculation 32 . In their study, the authors found that a C-terminal intrinsically disordered region of SS18 regulates its forming microscopic condensates under the condition of ectopic overexpression, and that the N-terminal 70aa of SS18 is required for its binding to CBAF.…”
Section: Discussionsupporting
confidence: 92%
“…3 – 5 ). In addition, we noted that the endogenous SS18 or SS18-SSX1 shows as a similar puncta-like distribution in mouse embryonic stem or synovial sarcoma cells as that of overexpression in HeLa, HEK293T, or synovial sarcoma cells 30 , 32 (Figs. 3 – 5 ).…”
Section: Discussionmentioning
confidence: 72%
“… SUPPORTING CITATIONS The following references are cited in the supplemental information : Cassandras et al, 2020 ; Chen et al, 2017 ; Frazier et al, 2019 ; Hagan et al, 2020 ; Huaqi et al, 2019 ; Jin et al, 2018 ; Kuang et al, 2021 ; Liu et al, 2018 ; Manchado et al, 2016 ; Maynard et al, 2020 ; Nakamura et al, 2015 ; Park et al, 2019 ; Treutlein et al, 2014 ; Wang et al, 2019 ; Wei et al, 2021 ; Wimmer et al, 2019 ; Wong et al, 2018 ; Zhang et al, 2021 . …”
mentioning
confidence: 99%
“…Based on these findings, we construct a robust and fast PST system, JUN TetON ESC [13]. Compared to other PST models (2-3 days) [9][10][11]14], JUN-induced PST takes within only 8 h (less than one cell cycle), more than 6 h JUN induction will lead an irreversible differentiation of mESCs [15], thus offering us a good opportunity to capture the key events of PST occurred in the early stage. Recently, we reported that SS18/BAFs play a critical role in JUN-induced PST [15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other PST models (2-3 days) [9][10][11]14], JUN-induced PST takes within only 8 h (less than one cell cycle), more than 6 h JUN induction will lead an irreversible differentiation of mESCs [15], thus offering us a good opportunity to capture the key events of PST occurred in the early stage. Recently, we reported that SS18/BAFs play a critical role in JUN-induced PST [15]. BAFs, also known as mammalian switch/sucrose nonfermentable(mSWI/SNF), initially found in S. cerevisiae, contain an enzyme subunit BRG1 or BRM serving the ATP-dependent chromatin remodeling function, as well as other regulatory subunits, like SS18 [16].…”
Section: Introductionmentioning
confidence: 99%